2020
DOI: 10.1017/s0025315420000120
|View full text |Cite
|
Sign up to set email alerts
|

Feeding habits of the franciscana dolphin (Pontoporia blainvillei) in south-eastern Brazil

Abstract: This study evaluated the feeding habits of the franciscana dolphin (Pontoporia blainvillei) in south-eastern Brazil. Stomach contents were collected from a total of 145 dead specimens found incidentally caught by fishing vessels or stranded between 2005 and 2015. Fish otoliths, cephalopod beaks and whole non-digested prey were used for prey species identification. A total of 9337 prey items were identified, including 26 species of teleost fishes and three species of cephalopods. The most important prey familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…Similar δ 13 C and δ 15 N values have also been observed based on muscle tissues of these species in the central coast of Rio de Janeiro in south-eastern Brazil (Baptista et al, 2016). This similarity in the isotopic ratios agrees with their local distribution, as both species are strongly associated with shallow waters and estuarine regions, where they feed mainly on small pelagic and demersal neritic prey (Di Beneditto et al, 2009;Campos et al, 2020). However, S. guianensis and P. blainvillei from southeastern Brazil differ in terms of prey preferences, as demonstrated in studies based on stomach contents.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Similar δ 13 C and δ 15 N values have also been observed based on muscle tissues of these species in the central coast of Rio de Janeiro in south-eastern Brazil (Baptista et al, 2016). This similarity in the isotopic ratios agrees with their local distribution, as both species are strongly associated with shallow waters and estuarine regions, where they feed mainly on small pelagic and demersal neritic prey (Di Beneditto et al, 2009;Campos et al, 2020). However, S. guianensis and P. blainvillei from southeastern Brazil differ in terms of prey preferences, as demonstrated in studies based on stomach contents.…”
supporting
confidence: 79%
“…However, S. guianensis and P. blainvillei from southeastern Brazil differ in terms of prey preferences, as demonstrated in studies based on stomach contents. While the main prey of S. guianensis include the banded croaker (Paralonchurus brasiliensis) and the cutlass fish (Lopes et al, 2012b), the diet of P. blainvillei is dominated by the American coastal pellona (Pellona haroweri) and the bigtooth corvina (Isopisthus parvipinnis) (Campos et al, 2020). Furthermore, the observed gradient in δ 13 C values may be explained by small-scale differences in areas used (Figueiredo et al, 2020), as S. guianensis were mainly sampled near the Cananéia estuary, while P. blainvillei samples were more uniformly distributed along the coast.…”
mentioning
confidence: 99%
“…The analyzed franciscana dolphins were enriched in 13 C compared to Guiana dolphins, which may indicate a greater dependence on benthonic sources in its diet. Although previous literature on stomach content analysis showed that both species preferentially fed on prey with demersal habits along their whole distribution (Danilewicz et al 2002, Rosas et al 2010, previous studies in the surveyed area have reported distinct fish species as the main ones for franciscanas (American coastal pellona, Pellona haroweri, and Bigtooth corvina, Isopisthus parvipinnis) and Guiana dolphins (Banded croaker, Paralonchurus brasiliensis, and Atlantic cutlassfish, Trichiurus lepturus) (Lopes et al 2012, Campos et al 2020. This difference in prey compositions may have influenced the δ 13 C and δ 15 N values, as these fish probably have distinct isotopic signatures.…”
Section: Discussionmentioning
confidence: 93%
“…Franciscanas feed on juveniles or smallsized prey, usually up to 15 cm (Di Beneditto & Ramos 2001), and Guiana dolphins consume prey with a greater variation in size, reaching up to 100 cm in length (Santos et al 2002). Previous studies have shown differences among several feeding items consumed by local franciscana and Guiana dolphins (Lopes et al 2012, Campos et al 2020, as well as distinct main preys when comparing the feeding habits of Guiana dolphins found dead inner estuarine waters and the ones found along the shoreline (Lopes et al 2012).…”
Section: Introductionmentioning
confidence: 97%
“…The results presented here share spectral and temporal details of the echolocation and burst pulse clicks of P. blainvillei from coastal waters in the southeastern Atlantic Ocean. When modeling the niche of local cetaceans, Figueiredo et al (2020) warned that onboard sightings were not the best tool when considering P. blainvillei , which was not sighted in an area of a large number of incidental captures (see Campos et al, 2020) where they are camouflaged by turbid waters. Thus, our descriptions of P. blainvillei acoustic parameters provide new tools for further investigations of this species occurrence in local waters using PAM.…”
Section: Figurementioning
confidence: 99%